A, The THE RELATIONSHIP BETWEEN BODY MASS INDEX (BMI) AND CHOLESTEROL LEVELS WITH THE INCIDENCE OF HYPERTENSION IN THE WORKING AREA OF WONOAYU HEALTH CENTER - Aan Syah Khusnan; Siti Maemonah; Alfi Maziyah; Kusmini Suprihatin (Global Ten Public Health and Nursing Journal, 2025)
Hypertension remains a major concern in the field of public health, with the incidence rate continuously increasing over time in Indonesia, including within the working area of Wonoayu Public Health Center, Sidoarjo Regency. Risk factors such as Body Mass Index (BMI) outside the normal range and high cholesterol levels are known to contribute to the occurrence of hypertension. This study was conducted to examine the correlation between BMI and cholesterol levels with the incidence of hypertension.This research employed a quantitative method with a cross-sectional design. The total sample consisted of 46 respondents, selected using the total sampling technique. Data were obtained through direct measurement and interviews, then analyzed using the Chi-Square test.The majority of respondents had obese BMI status (28.3%) and high cholesterol levels (41.3%). The most common hypertension levels were hypertensive crisis (33%) and stage 1 hypertension (28%). After data analysis using the Chi-Square test, a significant correlation was found between BMI and the incidence of hypertension (p = 0.018) as well as between cholesterol levels and the incidence of hypertension (p = 0.002).An increase in BMI and cholesterol levels is directly proportional to the degree of hypertension. Fat accumulation and atherosclerotic plaque formation can worsen blood pressure regulation. Therefore, health education regarding weight control and cholesterol management needs to be enhanced as a preventive effort against hypertension.